2015
DOI: 10.2105/ajph.2014.302489
|View full text |Cite
|
Sign up to set email alerts
|

Transdisciplinary Cardiovascular and Cancer Health Disparities Training: Experiences of the Centers for Population Health and Health Disparities

Abstract: The Centers for Population Health and Health Disparities program promotes multilevel and multifactorial health equity research and the building of research teams that are transdisciplinary. We summarized 5 areas of scientific training for empowering the next generation of health disparities investigators with research methods and skills that are needed to solve disparities and inequalities in cancer and cardiovascular disease. These areas include social epidemiology, multilevel modeling, health care systems or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 34 publications
0
17
0
Order By: Relevance
“…Thus, there is a critical need to develop and examine weight management and PA interventions among cancer survivors of racial/ethnic minority status to enhance outcomes and reduce disparities. Consideration of patients' environmental, cultural, and survivorship context is critical to the success of these efforts . Racial and ethnic minority survivors are more likely to live in areas characterized by high segregation, traffic density, and crime and by low neighborhood socioeconomic status and access to full‐service supermarkets and PA resources .…”
Section: Effective Approaches For Improving Weight Management and Pamentioning
confidence: 99%
“…Thus, there is a critical need to develop and examine weight management and PA interventions among cancer survivors of racial/ethnic minority status to enhance outcomes and reduce disparities. Consideration of patients' environmental, cultural, and survivorship context is critical to the success of these efforts . Racial and ethnic minority survivors are more likely to live in areas characterized by high segregation, traffic density, and crime and by low neighborhood socioeconomic status and access to full‐service supermarkets and PA resources .…”
Section: Effective Approaches For Improving Weight Management and Pamentioning
confidence: 99%
“…Indeed, others have called for the use of IS to reduce health disparities 3,[36][37][38] and increase the impact of health research. 39 The Centers for Population Health and Health Disparities program included implementation research as a requisite skill for researchers in cardiovascular disease and cancer in order to address the complexity of observed disparites.…”
Section: Addressing Health Disparities Through Implementation Sciencementioning
confidence: 99%
“…39 The Centers for Population Health and Health Disparities program included implementation research as a requisite skill for researchers in cardiovascular disease and cancer in order to address the complexity of observed disparites. 37 Within public health genomics, the Genomics and Public Health Action Collaborative has identified objectives and metrics for HBOC and LS that include an IS framework and implementation outcome measures. 40 Moreover, systematic reviews of the literature 41 and an National Institutes of Health research portfolio 41 have demonstrated an ongoing need to incorporate implementation science into genomic medicine research.…”
Section: Addressing Health Disparities Through Implementation Sciencementioning
confidence: 99%
“…Despite increasing interest and efforts to improve health outcomes among Latinos, the imbalance between the proportion of Latinos in the public health workforce and their representation in the general U.S. population is a persistent challenge (Rodriguez et al, 2014). The lack of public health training in transdisciplinary and multilevel approaches is halting progress in reducing health disparities (Golden et al, 2015; Rodriguez et al, 2014). …”
Section: Introductionmentioning
confidence: 99%